Dalam IDEOLOGI PENDIRIAN ORGANISASI MUHAMMADIYAH DALAM NASKAH "MA HUWA ASASUL JAMIATUL MUHAMMADIYAH": Naskah “Ma Huwa Asasul Jamiatul Muhammadiyah” - Akbar, Doni Wahidul; Liza, Fitri; Hakim, Ahmad Luqman; Doni Wahidul Akbar (Jurnal Lektur Keagamaan, 2024)
The Muhammadiyah organization was founded with the slogan of renewal and modernization. These two slogans make Muhammadiyah different from other organizations. The text "Ma Huwa Asasu Jam'iatul Muhammadiyah" explains Ahmad Dahlan's sermons and describes the basis and concerns of Ahmad Dahlan regarding the condition of Muslims who deviate from the teachings of the Qur'an and Hadith. This study used the paradigm of philology and hermeneutics as a humanities science, namely, a science that carries out a hermeneutic function by correcting texts as social discourse. Text analysis, especially single manuscript editions, uses descriptive analysis methods. The handling of the text "Ma Huwa Asasul Jamiatul Muhammadiyah" requires careful content analysis by considering various specific cases in the text and the nature of its intertextuality. This study found three major principles of Ahmad Dahlan's ideology. First is the ideology of the Muhammadiyah organization. Second, Ahmad Dahlan's reasons for establishing Muhammadiyah. Third, Ahmad Dahlan's message to the people of Pekajangan, Pekalongan, Central Java. This research aims to provide information about the founding of the Muhamadiyah organization contained in the text. Then, it examines in depth how Ahmad Dahlan's ideology established the Muhammadiyah organization. In addition, it reveals the implied content of Ahmad Dahlan's sermon. This is necessary so that the cadres and the people understand the embryo of the Muhammadiyah organization.